Asymmetry Relationship between Economic Growth and Unemployment Rates in the Arab countries: Application of the OKUN Law during 1960-2017 - Louail, Bilal; Ben Haj Hamida Hayed (Zielona Góra: Faculty of Economics and Management Press)
A well-known macroeconomic relationship is called the OKUN Law, which states that the negative correlation between unemployment rates and raw domestic output can be determined. This study will focus on the theoretical framework for developing models of the elationship between economic growth and unemployment rates.
Keywords: Okun Law; gross domestic product; unemployment rate; Arab countries; prawo Okuna; produkt krajowy brutto; stopa bezrobocia; kraje arabskie